Efecto de la adición de biosólido (seco) a una pasta cerámica sobre la resistencia mecánica de ladrillos (2015)
Sewage sludge was added as part of ceramic slurry for making bricks. Raw materials (clay and sludge) were characterized in terms of chemical composition, mineralogical phases, thermal behavior and physical characteristics. Test tiles with up to 15% inclusion of sludge in the dry state of standard dimensions according Norma Técnica Colombiana (NTC) 296 and calcined at temperatures of 950 °C, 1000 °C and 1050 °C. In accord of the NTC 4017, compression resistance test, were performed in order to evaluate the effect on this property has the percentage amount of addition of the sludge. From environmental point of view, the safety of metals in sludge was evaluated by developing the Toxicity Characteristic Leaching Procedure (TCLP) test bricks made with the addition of the residue.